EVALUATION OF ANTIBACTERIAL ACTIVITY OF PHYCOCYANIN PEPTIDES FROM SPIRULINA PLATENSIS THROUGH MULTIPLE MOLECULAR DOCKING STUDY - Arindita, Ni Putu Yunika; Munawaroh, Heli Siti Halimatul; Aisyah, Siti; Khoiriah, Selmi Fiqhi (BRIN - Badan Riset dan Inovasi Nasional, 2023)
Peptides derived from the phycocyanin pigment of Spirulina plantesis were screened to identify potential natural antibacterial candidates. In silico protein hydrolysis was performed to obtain active peptides, and a multiple molecular docking (MLD) approach was used to to predict the synergistic mechanisms of various peptide combinations with their respective receptors. Nine phycocyanin peptides showed interaction values ranging from -5.1 to -6.0 kcal/mol, compared to the native ligand (BB-78485) with a value of -9.7 kcal/mol. The results demonstrated a synergistic effect, as the binding affinity of peptide combinations exceeded that of individual peptides and the native ligand. Hydrophobic bonds and van der Waals forces played a crucial role in binding to the active site of 2VES proteins. However, ADME studies revealed that two peptides, YCL and ASYF, had poor pharmacokinetic properties. Overall, this study highlights the potential of phycocyanin peptides as antibacterial agents through the application of MLD.